Pengaruh jenis pengemulsi terhadap karakteristik fisik, total karotenoid dan sifat organoleptik mayones dari minyak buah merah (Pandanus conoideus Lamk.) degumming - Yunita Fransisca; Budi Santoso; Zita Letviany Sarungallo (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Mayonnaise is an emulsion product consisting of oil, water and other ingredients which affect its stability. Improving the stability of mayonnaise can be done by using emulsifiers and stabilizers. This study aims to determine the type and concentration of the right emulsifier to produce a stable red fruit oil mayonnaise and to analyze the physical properties, total carotenoids, and organoleptic properties of the red fruit oil mayonnaise. In this study, degummed red fruit oil was used because the impurity components (gum and phospholipids) had been removed. The experimental design used in this study was a completely randomized design (RAL) with four different treatments of emulsifier, namely Gelatin 3.5% (M1), Gelatin: Lecithin = 3.0%: 0.5% (M2), Gelatin: Gum Arabic = 2.0%: 1.5% (M3), and Gelatin: Gum Arabic: Lecithin = 1.5%: 1.5%: 0.5% (M4) with three replications for each treatment. The results showed that the degummed red fruit oil mayonnaise of the four formulas produced varied in color from red, pink, orange, and dark orange, had a distinctive aroma of mayonnaise and a sour taste of mayonnaise (pH 4.31-5.20), had a thick texture (viscosity 220-297 d.Pas) with a total carotenoid content ranging from 3170.9-3410.1 ppm. The organoleptic properties (level of preference) of the four mayonnaise formulas produced include color having a score of 5.12-5.88 (like moderately), aroma with a score of 4.48-5.28 (neutral - like moderately), the texture of 5.00-5.40 (like moderately - like), taste ranges from 4.72-5.12 (neutral - like moderately), and the overall rating ranges from 5.08-5.64 (like moderately-like). Formula M1 (gelatin) and M3 (a combination of gelatin and gum arabic) can produce stable mayonnaise compared to other formulas.